Cell-free and concentrated pleural effusion reinfusion therapy with aggressive nutritional support improved refractory pleural effusion in a patient with malnutrition after distal gastrectomy for gastric cancer - Masanobu Usui; Manami Matsumoto; Yoshinori Itani; Norimasa Tsuzuki; Miyo Murai; Akihiro Ito; Akihiko Futamura (Fujita Medical Journal)
An 82-year-old man underwent distal gastrectomy for gastric cancer 6 months before admission to our hospital. His postoperative food intake was reduced to less than half of the preoperative amount. Two months postsurgery, he fell and fractured his leg and was bedridden. Furthermore, hypoalbuminemia and bilateral pleural effusions persisted. Despite repeated administration of an albumin preparation and pleural drainage, he showed no improvement for 3 months and was referred to our hospital. On admission, his height was 171 cm, weight 52.8 kg, and body mass index 18.1 kg/m2. Moreover, he was clearly undernourished and had difficulty maintaining a standing position. In terms of nutritional enrichment, his diet was adjusted to meet the needs of an older adult patient postgastrectomy. A protein-enriched supplemental diet of approximately 1800 kcal was planned, and he could consume almost the entire amount. His refractory pleural effusion was resolved by performing concentrated pleural effusion reinfusion therapy, and he continued to receive aggressive nutritional support and rehabilitation. The patient’s general condition and activities of daily living improved markedly. Subsequently, he was discharged and could walk independently on day 64 of hospitalization. Summary: We experienced a successful case of refractory pleural effusion due to malnutrition treated with aggressive nutritional support combined with concentrated pleural fluid filtration reinfusion therapy.